A medium-throughput protease assay for screening green plant material - Stonoha-Arther, Christina; Molodchenko, Andrew; Panke-Buisse, Kevin (Frontiers in Sustainable Food Systems, 2025)
Aboveground plant material is subject to stress-induced senescence after harvest. For flowers, vegetables and forages, this process can severely impact quality. Proteases, in particular, are responsible for post-harvest protein degradation and contribute to cellular breakdown. Alfalfa is a high-quality forage and a perennial source of protein for dairy cows. Its nutritional value and suitability for sustainable agricultural production are also driving interest in the possible use of alfalfa for human consumption, however, the issue of rapid protein degradation after harvest needs to be addressed before the protein can be extracted for human use on a large scale. We have optimized a cost-effective, medium-throughput, fluorescence intensity-based protease activity assay specifically for aboveground plant tissue that balances precision and throughput, the latter of which has been a barrier to further study. This method will allow higher-throughput phenotyping of plant protease activity than is currently feasible: one person can process approximately 120 samples per day, compared to approximately 25 with previous methods. We have used this method in alfalfa to assess protease activity during wilting at pH 7.4 and pH 6.3.